Local knowledge surveys with small‐scale fishers indicate challenges to sawfish conservation in southern Papua New Guinea. Issue 10 (5th August 2021) - Grant, Michael I.; White, William T.; Amepou, Yolarnie; Baje, Leontine; Diedrich, Amy; Ibana, Dotty; Jogo, Dick J.; Jogo, Stanley; Kyne, Peter M.; Li, Owen; Mana, Ralph; Mapmani, Nigel; et al.
Abstract: Sawfish (Pristidae) are considered to be among the most threatened families of elasmobranch (sharks and rays). There is a need to gather information on the status of poorly known sawfish populations to assist in global recovery initiatives. This study used interviews with local fishers to investigate the presence of sawfish in southern Papua New Guinea (PNG) and their interactions with and uses and values for small‐scale fishers. A range of sawfish size classes are still encountered throughout southern PNG, while juvenile largetooth sawfish Pristis pristis were additionally reported in the freshwater reaches of all rivers surveyed. Reports of large size classes in estuarine and marine environments provide an optimistic outlook that sawfish populations persist throughout southern PNG. Most fishers that catch sawfish retain them for various uses including consumption and for the sale of meat, fins and occasionally rostra. Negative population trends including decreases in catch frequency and/or size classes were reported by 66% of interviewees, with the largest declines being reported in the Kikori River. The increasing technical capacity of small‐scale fishers, their preference for gillnetting and the emerging market for teleost swim bladder (a high‐value fishery product) present a major ongoing threat to sawfish in southern PNG. Furthermore, the tendency of fishers to kill or remove rostra from entangled sawfish results in high fishing mortality regardless of any use by the fisher. This study indicates that considerable community engagement will be necessary to manifest any legislative actions or increased enforcement on international trade regulations for sawfish in PNG. This is due to traditional land and waterway ownership values throughout PNG and the local perception of sawfish as a traditional food resource rather than an animal of intrinsic biodiversity value as perceived by global conservationists. Future research should consider exploring culturally appropriate conservation initiatives that are likely to achieve engagement and participation from local fishers.